Dipolar spin–spin coupling as an auxiliary tool for the structure determination of small isolated molecules. Issue 25 (15th June 2022) - Bizzocchi, Luca; Alessandrini, Silvia; Melosso, Mattia; Puzzarini, Cristina
Abstract : Dipolar spin–spin coupling constants, when combined with rotational constants, guarantee an improved structural determination. Abstract : The "gold standard" for obtaining accurate equilibrium structures is the so-called semi-experimental (SE) approach, which exploits the structural information contained in rotational constants. Within the SE approach, ground-state rotational constants—accurately obtained from high-resolution spectroscopic studies—are computationally corrected in order to remove vibrational effects. The resulting SE equilibrium rotational constants for a significant set of isotopic species allow for retrieving a unique set of equilibrium bond lengths and angles for the molecule under consideration. However, in some cases, the lack of isotopic substitution hampers or even prevents a rigorous and complete structure determination. In this perspective, we introduce the use of dipolar spin–spin coupling constants as an additional source of structural information in support of the standard SE approach. As a proof-of-concept, we tested this new strategy on some prototypical species, such as water, ammonia, phosphine, and their fluorinated counterparts. Our results indicate that—even when the molecular structure can be obtained from a large set of isotopic rotational constants—the use of dipolar spin–spin coupling constants guarantees a better accuracy and reduces the correlations among the geometrical parameters. Moreover, we point out that our approach offers the possibility to fully derive the molecular structure of PF3, a species for which any isotopic substitution is not possible.